RETOLD: Unlocking the potential of archaeological house reconstructions by standardizing documentation in open-air museums – experiences from the Museumsdorf Düppel in Berlin, Germany - Julia Heeb; Svea Röbke (EXARC Journal)
The Museumsdorf Düppel – a medieval archaeological open-air museum in Berlin – is a good example a bottom-up museum project from the 1970’s. The idea to create an open-air museum was born after the excavation of a medieval settlement had brought to light several house features, wells and objects ranging from pottery sherds to iron artefacts, in south-western Berlin. However, the museum institutions as well as the city council were not interested, paving the way for the foundation of a volunteer society. Founded in 1975, the friend’s society for the Museumsdorf Düppel began building houses, making pottery, and rediscovering the different techniques of medieval textile production amongst other crafts, with volunteers coming from a variety of backgrounds. Although the city council eventually began to fund the museum project, the hard work was carried out by amateur enthusiasts with a strong passion for learning and presenting medieval building techniques and crafts to the public. Without these idealists, the Museumsdorf Düppel would not exist today.